Development of Learning Media for Acehnese Culture Picture Books to Get to Know Local Culture in Early Childhood - Mutmainnah, Mutmainnah; Nessa, Rahmatun; Bukhari, Bukhari; Farhana Mohd Radzif, Nur; Kurniawati, Rizki (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2021)
Purpose – This research aims to see the development of picture book learning media with the theme of Acehnese culture to stimulate children to know the local culture.Design/methods/approach – This type of research is research and development or often referred to as Research and Development (R&D). The type of data in this research and development consists of two types of data, namely qualitative and quantitative data. Researchers took qualitative data by conducting observations, interviews, and documentation. The quantitative data were obtained from research respondents, which included: material experts, media experts, cultural experts, and learning media users.Findings – The development of picture book media is designed using Corel Draw with design layouts, picture illustrations, smoothing snaps, giving and giving to content/material experts, media experts, and cultural experts to find out the media that has been designed. The results of the experts get a percentage of 100%, media experts get a percentage of 96%, cultural experts get a percentage of 96%, small-scale trials are 3.9, and large-scale trials are 4.6.Research implications/limitations – Based on developing the media and testing the learning media for picture books with the theme of Acehnese culture to stimulate children to know the local culture of Aceh. Constraints faced related to internet connection and mastery of using Corel Draw in designing books.Practical implications – This research contributes in-depth knowledge that the media for learning books with the theme of Acehnese culture can stimulate children to get to know the local culture.Originality/value – This research contributes to understanding and introducing Acehnese culture from early childhood education as a basis for children not to forget the cultures that developed in Aceh. Paper type Research paper